Hypertrophic Cardiomyopathy in an Infant of a Diabetic Mother: A Case Report and Neonatal Surgical Perspective - Josh, G.D. Sushintha; Josh, G.D. Annora; Ramesh, Shanthi (Journal of Neonatal Surgery, 2025)
Background: Hypertrophic cardiomyopathy (HCM) in neonates is a rare and clinically heterogeneous disorder. A recognized cause in the neonatal period is maternal diabetes, particularly pre-gestational diabetes. Infants of Diabetic Mothers (IDMs) are at increased risk of transient myocardial hypertrophy, especially of the interventricular septum. Case Presentation: We present a neonate born to a mother with poorly controlled pre-gestational diabetes, who was diagnosed postnatally with HCM based on echocardiography showing significant septal hypertrophy and left ventricular outflow tract (LVOT) narrowing. The infant was managed conservatively with beta-blockers, with clinical and echocardiographic improvement over follow-up. Conclusion: HCM in IDMs is typically transient and responsive to medical therapy. However, distinguishing this from genetic or obstructive HCM is crucial, especially in the neonatal period where surgical intervention may be warranted. Awareness of such presentations is vital for neonatal teams, including pediatric surgeons, cardiologists, and intensivists.